Batch and fixed-bed column studies for biosorption of Zn(II) ions onto pongamia oil cake (Pongamia pinnata) from biodiesel oil extraction. (1st December 2015) - Shanmugaprakash, M.; Sivakumar, V.
Abstract: The present work, analyzes the potential of defatted pongamia oil cake (DPOC) for the biosorption of Zn(II) ions from aqueous solutions in the both batch and column mode. Batch experiments were conducted to evaluate the optimal pH, effect of adsorbent dosage, initial Zn(II) ions concentration and contact time. The biosorption equilibrium and kinetics data for Zn(II) ions onto the DPOC were studied in detail, using several models, among all it was found to be that, Freundlich and the second-order model explained the equilibrium data well. The calculated thermodynamic parameters had shown that the biosorption of Zn(II) ions was exothermic and spontaneous in nature. Batch desorption studies showed that the maximum Zn(II) recovery occurred, using 0.1 M EDTA. The Bed Depth Service Time (BDST) and the Thomas model was successfully employed to evaluate the model parameters in the column mode. The results indicated that the DPOC can be applied as an effective and eco-friendly biosorbent for the removal of Zn(II) ions in polluted wastewater. Highlights: The potential of pongamia oil cake for biosorption of Zn(II) was investigated. The functional groups for biosorption was revealed by FTIR. Elution was efficiently eluted with EDTA at pH 5.0. The removal of Zn(II) ions was dependent on bed height, flow rate and initial metal concentration.